Legal Review of the Role of Prosecutors in Optimizing the Increase in Criminal Sanctions Against Pedophiles (Research Study at the Wajo District Attorney's Office) - Panjaitan, Tiara Robena; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Abstract. However, can the actualization of the role of the Prosecutor in implementing court decisions in the form of chemical castration be realized fluently, considering the considerations from various parties that lead to contradictions that are involved in the support system in implementing chemical castration sentences against pedophiles. The aim of this research is to find out and analyze (1) a review of national criminal law on the implications of pedophilia with child protection law, (2) the problems for prosecutors in implementing heavy criminal sanctions for pedophilia perpetrators, (3) the concept of effective legal supremacy in overcoming the problems of implementing heavy criminal sanctions for pedophilia perpetrators. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data sources used are primary data and secondary data. Primary data is data obtained directly from the field or from the first source and has not been processed by other parties. Based on the results of the research and discussion, it can be concluded: (1) There are no laws and regulations in Indonesia that specifically mention the crime of pedophilia, only that laws and regulations, especially Law Number 35 of 2014 concerning Child Protection in Articles 81 and 82, have explained the punishments that will be imposed on perpetrators of sexual deviations who make children their victims. (2) In the execution of chemical castration, the Prosecutor is not an expert in health, so the Prosecutor's Office collaborates with the IDI (Indonesian Doctors Association) to carry out the execution of the sentence, because the IDI is considered the most competent in carrying out punishments with medical elements. Theoretically, the implementation of chemical castration has been properly regulated in PP Number 70 of 2020, but it is different from the situation in the field. (3) That the Fatwa of the Medical Ethics and Honorary Council (MKEK) Number 1 of 2016 concerning Chemical Castration needs to be reviewed again because there are already regulations in the Republic of Indonesia Government Regulation Law Number 70 of 2020 concerning Procedures for Implementing Chemical Castration, Installation of Electronic Detection Devices, Rehabilitation, and Announcement of the Identity of Perpetrators of Sexual Violence Against Children.